The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1371/journal.pone.0248590
|View full text |Cite
|
Sign up to set email alerts
|

How does spectator presence affect football? Home advantage remains in European top-class football matches played without spectators during the COVID-19 pandemic

Abstract: The present paper investigates factors contributing to the home advantage, by using the exceptional opportunity to study professional football matches played in the absence of spectators due to the COVID-19 pandemic in 2020. More than 40,000 matches before and during the pandemic, including more than 1,000 professional matches without spectators across the main European football leagues, have been analyzed. Results support the notion of a crowd-induced referee bias as the increased sanctioning of away teams di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
96
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 50 publications
14
96
3
1
Order By: Relevance
“…For example, Bryson et al (2021) found that the absence of a crowd had no significant effect on the final score, whereas Schlenker et al (1995) reported significantly fewer points gained at home in Germany and Spain without the support of a crowd, but that no such effects existed in Austria, Italy, and England. Wunderlich (2021) goes as far to conclude that the HApersists in the absence of crowds; although these findings may be of direct consequence to the substantial heterogeneity brought about via comparing games in the last season against those up to 10 years ago. On the other hand, both Schlenker, Phillips, Boniecki, and Schlenker (1995) , Tilp and Thaller (2020) and Hill and Van Yperen (2021) assert that HA is heavily reliant on the presence of fans, as points, goals and shots at goal, were significantly reduced for home teams in the during-COVID period.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Bryson et al (2021) found that the absence of a crowd had no significant effect on the final score, whereas Schlenker et al (1995) reported significantly fewer points gained at home in Germany and Spain without the support of a crowd, but that no such effects existed in Austria, Italy, and England. Wunderlich (2021) goes as far to conclude that the HApersists in the absence of crowds; although these findings may be of direct consequence to the substantial heterogeneity brought about via comparing games in the last season against those up to 10 years ago. On the other hand, both Schlenker, Phillips, Boniecki, and Schlenker (1995) , Tilp and Thaller (2020) and Hill and Van Yperen (2021) assert that HA is heavily reliant on the presence of fans, as points, goals and shots at goal, were significantly reduced for home teams in the during-COVID period.…”
Section: Discussionmentioning
confidence: 98%
“…In the scientific literature, there is strong support for the hypothesis that the home advantage can be largely explained by social pressure on the referees, emanating from the present audience, attributed mainly to the noise the crowd produces in favor of the home team during games. Questions such as whether referees tend to favor the home team or disadvantage the away team are still subject of ongoing discussions (e.g., Pollard, 2008 ; Sors et al, 2020 ; Leitner et al, 2021 ; Wunderlich et al, 2021 ). From psychological and evolutionary perspectives, an explanation for the home advantage effect, based on social pressure and conformity are logical and comprehensible.…”
Section: Introductionmentioning
confidence: 99%
“…By now, there are numerous studies from various fields regarding the effects of the COVID-19 pandemic on football, some of them concentrating on the home advantage effect. Overall, most of these studies indicate that the home advantage tends to decline when games are played behind closed doors (Bryson et al, 2020 ; Dilger and Vischer, 2020 ; Fischer and Haucap, 2020 ; Follert et al, 2020 ; McCarrick et al, 2020 ; Sors et al, 2020 ; Hill and Van Yperen, 2021 ; Konaka, 2021 ; Leitner et al, 2021 ; Sánchez and Lavín, 2021 ; Santana et al, 2021 ; Scoppa, 2021 ; Wunderlich et al, 2021 ). In this context, Bryson et al ( 2020 ) state e.g., that “ without a crowd, fewer cards were awarded to the away teams, reducing home advantage [and that] these results have implications for the influence of social pressure and crowds on the neutrality of decisions.” Other findings indicate that ghost games might also have a direct effect on the (non-verbal) behavior of professional football players, staff and officials on pitch during games (Leitner and Richlan, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rare cases where they have been examined concurrently, the assumed mechanism (e.g. indirect influence of the crowd on results through team and referees' performance) has not been specified 13,29,[38][39][40][41] .…”
Section: Problems With Previous Accounts Of Hamentioning
confidence: 99%